2014
DOI: 10.3402/rlt.v22.22797
|View full text |Cite
|
Sign up to set email alerts
|

Students’ engagement with a collaborative wiki tool predicts enhanced written exam performance

Abstract: We introduced voluntary wiki-based exercises to a long-running cognitive psychology course, part of the core curriculum for an undergraduate degree in psychology. Over 2 yearly cohorts, students who used the wiki more also scored higher on the final written exam. Using regression analysis, it is possible to account for students' tendency to score well on other psychology exams, thus statistically removing some obvious candidate third factors, such as general talent or enthusiasm for psychology, which might dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
(47 reference statements)
0
5
0
1
Order By: Relevance
“…For example, wikis were effectively used as course management tool in undergraduate courses (Zorko, 2009;Bradley et al, 2010). Stafford et al (2014) introduced wiki-based exercises to a long-running cognitive psychology course. Over two yearly cohorts, they found that the students who participated in the wiki collaborative tasks scored higher on the final written exam.…”
Section: Educational Approaches Of Wikismentioning
confidence: 99%
“…For example, wikis were effectively used as course management tool in undergraduate courses (Zorko, 2009;Bradley et al, 2010). Stafford et al (2014) introduced wiki-based exercises to a long-running cognitive psychology course. Over two yearly cohorts, they found that the students who participated in the wiki collaborative tasks scored higher on the final written exam.…”
Section: Educational Approaches Of Wikismentioning
confidence: 99%
“…Overall, they found a limited collaboration among the participants using the wiki, while they did bulk of their discussion and sharing of ideas via email. [21] also engaged 216 students in voluntary wiki writing over a period of two years, at the end of which their exam performance was used to judge the benefits of wiki writing. Their findings showed that students who were actively involved in the wiki writing performed better than the less active students in their final exams.…”
Section: Related Workmentioning
confidence: 99%
“…Their findings showed that students who were actively involved in the wiki writing performed better than the less active students in their final exams. One short coming of this study is that little or no emphasis was placed on participation in the wiki writing and there was no incentive to motivate participants to contribute [21]. [11] assessed students' collaborative learning behaviour using wiki.…”
Section: Related Workmentioning
confidence: 99%
“…Junco et al (2011) applied ANOVA to calculate the impact on learning outcome and student engagement using twitter [13]. Stafford et al (2014) examined the wiki activity indicators and the final grades of the students [14]. The results showed that there was significant correlation among the two variables and students who were engaged with wiki activities acquired better overall score.…”
Section: Introductionmentioning
confidence: 99%